Between altruism and self-aggrandisement: Transparency, accountability and politics in Ghana's oil and gas sector. (October 2020) - Ackah, Ishmael; Lartey, Abraham; Acheampong, Theophilus; Kyem, Eric; Ketemepi, Gifty
Abstract: Effective governance of oil and gas resources has been identified as the thread that divides altruistic and self-aggrandising behaviour in petroleum producing countries. Indeed, the choice of governance attitude has consequences on how oil and gas resources are translated into sustainable development.This study assesses the governance framework that was in place before the oil and gas find in Ghana and those that have been put in place during the production era. We then explore the performance of Ghana on key global governance indicators before and after the oil find, namely the Mo Ibrahim Governance Index, Corruption Index and the Resource Governance Index. The following reasons motivate the focus on Ghana in this study: firstly, the IMF predicts that Ghana will be one of the fastest-growing economies in the world in 2019 and beyond, mainly due to the coming on stream of new oil and gas fields. Secondly, the country is relatively politically stable compared to other countries in the region. The findings indicate that emphasis is placed on the enactment of laws and policies and to some extent, evidence that these laws are implemented. However, the passage of laws does not guarantee good governance. Often, the missing link is how the laws are implemented. Since some of these laws have discretionary provisions, there are chances that individual and institutional actors can exhibit self-aggrandising behaviour. Global governance indices therefore need to consider how these laws are implemented and their potential impact on the governed.